An Ecological Theology of Liberation Salvation and Political Ecology - Castillo, Daniel Patrick (Orbis Books, 2019)
Catholic Press Association Book Award Honorable Mention Catholic Social Teaching  "Here, in this global garden, we are all invited to continue to be an expression and parable of the Imago Dei as gardeners, carers and advocates of all creation as we become a concrete sign of the Kingdom of God here on Earth. The reading of the book is fluid, pleasant and carries the academic rigour necessary to be a widely read and used work in the academy." -- Paulo Ueti, Journal of Theology for Southern Africa  Castillo's book is an important scholarly work that offers an attractive vision of a political ecology rooted in and fertilized by the creative wisdom of God.--Hilda P. Koster, Modern Theology, University of St. Michael's College, University of Toronto  What is the relationship between salvation, human liberation, and care for creation? To answer this question Daniel Castillo expands on the ideas presented in Gustavo Gutiérrez's classic work A Theology of Liberation and proposes a novel concept: green liberation theology. In this compelling and original work Castillo places Gutiérrez in dialogue with a diverse array of theological, ecological, and socio-scientific discourses, drawing upon the work of Jon Sobrino, Willie James Jennings, Walter Brueggemann, Ellen Davis, and others, paying special attention to Pope Francis' encyclical Laudato Si'.